Emulation of X-ray Light-Field Cameras - Nicola Viganò; Felix Lucka; Ombeline de La Rochefoucauld; Sophia Bethany Coban; Robert van Liere; Marta Fajardo; Philippe Zeitoun; Kees Joost Batenburg (Journal of Imaging, 2020)
X-ray plenoptic cameras acquire multi-view X-ray transmission images in a single exposure (light-field). Their development is challenging: designs have appeared only recently, and they are still affected by important limitations. Concurrently, the lack of available real X-ray light-field data hinders dedicated algorithmic development. Here, we present a physical emulation setup for rapidly exploring the parameter space of both existing and conceptual camera designs. This will assist and accelerate the design of X-ray plenoptic imaging solutions, and provide a tool for generating unlimited real X-ray plenoptic data. We also demonstrate that X-ray light-fields allow for reconstructing sharp spatial structures in three-dimensions (3D) from single-shot data.